1993
DOI: 10.1111/j.1570-7458.1993.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant water stress on honeydew production, weight gain and oviposition of brown planthopper Nilaparvata lugens on rice cultivars

Abstract: Glasshouse studies were made on honeydew production, adult and nymphal body weight gain, fecundity and size of egg groups of brown planthopper Nilaparvata lugens (Stål) (Homoptera: Delphacidae) (BPH) on CVS TN1, ASD7, Babawee, Mudgo, Rathu‐Heenati and Ptb33 rice plants with watering regimes of 10 ml, 20 ml, 30 ml and excess water daily. Honeydew production, weight gain, fecundity and size of egg groups were greatest on TN1, followed by ASD7. BPH did less well on Babawee, Mudgo and Rathu‐Heenati and they did wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Young, pre-tillering rice plants tend to be silicon deficient ( Ma et al, 1989 ); therefore, pre-tillering rice should be expected to make a higher investment in anti-herbivore resistance particularly in varieties with major resistance genes. However, several studies suggest that this is generally not the case, but that older rice plants often become increasingly resistant to herbivores, particularly planthoppers and leafhoppers ( Rapusas and Heinrichs, 1982 , Baqui and Kershaw, 1993 , Horgan et al, 2016b , Srinivasan et al, 2015 , Srinivasan et al, 2016 ). The results from the present study confirm that pre-tillering plants are more susceptible than tillering rice plants, even in IR62.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young, pre-tillering rice plants tend to be silicon deficient ( Ma et al, 1989 ); therefore, pre-tillering rice should be expected to make a higher investment in anti-herbivore resistance particularly in varieties with major resistance genes. However, several studies suggest that this is generally not the case, but that older rice plants often become increasingly resistant to herbivores, particularly planthoppers and leafhoppers ( Rapusas and Heinrichs, 1982 , Baqui and Kershaw, 1993 , Horgan et al, 2016b , Srinivasan et al, 2015 , Srinivasan et al, 2016 ). The results from the present study confirm that pre-tillering plants are more susceptible than tillering rice plants, even in IR62.…”
Section: Discussionmentioning
confidence: 99%
“…Since plants face distinct challenges as they grow and develop, they are predicted to shift their defence strategies to counter their most probable biotic stresses ( Price, 1991 , Herms and Mattson, 1992 ). Resistance to planthoppers in rice may increase or decrease during plant development ( Rapusas and Heinrichs, 1982 , Baqui and Kershaw, 1993 , Vu et al, 2014 , Horgan et al, 2016b ) presumably depending on underlying resistance mechanisms or resistance genes ( Srinivasan et al, 2015 , Srinivasan et al, 2016 ). Therefore, the age at which plants are attacked, how resistance changes over plant development and how farmers manage their crop (vis-à-vis fertilizer and pesticide inputs) represent key determinants of planthopper population growth and damage responses in fields of resistant rice.…”
Section: Introductionmentioning
confidence: 99%
“…BPH feeding on susceptible rice varieties generally produce copious amounts of honeydew droplets rich in amino acids which can be detected using the ninhydrin technique whereas on resistant varieties honeydew production is considerably lower (Padgham & Woodhead, 1989). Other workers have shown that the volume of honeydew, as measured by calibrated micropipette, produced on resistant varieties is lower than on susceptible rice (Paguia et al, 1980;Baqui & Kershaw, 1993). These results are in agreement with those reported here although the former were obtained from in planta studies whereas the present work relates to in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in honeydew production could indicate declining feeding efficiency as a result of reduced ingestion rate, osmotic regulation, or a combination of the two (Nalam et al ., 2020). Some studies have shown that honeydew production by phloem feeding insects declines when feeding on water‐limited plants (Issacs et al ., 1998; Hale et al ., 2003), but the field is lacking in studies and consensus (Baqui & Kershaw, 1993; Tan et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%